Thermal and magnetic property behaviors of a binary alloy borophene structure: A Monte Carlo study. (December 2020) - Sahdane, T.; Qajjour, M.; Maaouni, N.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Benomar, W. Ousi
Abstract: In this work, we investigate the magnetic properties of a binary alloy borophene structure of the form Ap B1-p . The calculations were performed using the Monte Carlo method under the Metropolis algorithm. The studied borophene structure consists of atoms A of spin S = 5/2 with a concentration p and atoms B of spin σ = 2 with a concentration 1-p. The Hamiltonian of the system includes the ferrimagnetic coupling between A and B atoms. The behavior of the total and partials magnetizations are explored for different values of the concentration p. In addition, under specific values of the physical parameters and the concentration p, we study the possibility of the appearance of the compensation point. Besides, The hysteresis cycles have been established and discussed.